Immigrant entrepreneur firm start-up behavior and reasoning : a reflective study of causation, effectuation and bricolage - Mammadov, Kanan (2013)
Entrepreneurship research studies how and why firms come into being, survive and grow (Davidsson, 2004; Gartner, 1985; Schumpeter, 1934). Early literature has proposed a linear model of entrepreneurship which is intentional (Bird, 1988), opportunity discovery (Kirzner, 1997; Shane and Venkataraman, 2000) and goal & strategy oriented (Wiklund & Shepherd, 2005). Being a mainstream in the earlier research, it is labelled as causation model by Sarasvathy (2001). Several scholars such as Baker & Nelson (2005) and Sarasvathy (2001a, b; 2008) questioned the validity of the model and proposed two additional models to the classic model: Effectuation (Sarasvathy, 1998) and Entrepreneurial Bricolage (Baker & Nelson, 2005). These models claim that entrepreneurs not only start by planning the ends and exploit opportunities, however they start with means at hand which drive them to different ends.